O terror e a dádiva. Pedro Paulo Gomes Pereira. Editora Vieira, Goiânia, 2004. - Milstein, Diana (Avá. Revista de Antropología. PPAS. UNaM. Misiones. Argentina., 2026)
La sección reseñas no incluye resumen.